Perancangan Aplikasi Kasir Berbasis Website Menggunakan Barcode Reader Pada Toko Mulia Pancing - Dini Vita Aspuri; Saputra, Herlambang; Azro, Isnainy (Teknik Komputer Politeknik Negeri Sriwijaya, 2025)
Toko Mulia Pancing is a small and medium business that provides a wide selection of goods and tools for fishing. Financial management processes such as recording transactions and processing stock data are still done manually so errors often occur. This website, named